De Nederlandse identiteit in de kunst na 1945. - Dippel, Rini; Fritz-Jobse, Jonneke; Gribling, Frank; Imanse, Geurt; Lubbers, Frank; Ruhé, Harry; Stokvis, Willemijn; Stumpel, Jeroen; Wesseling, Janneke; van Grootheest, Tijmen; van der Heijden, Marijke (Amsterdam : Uitgeverij Uniepers Abcoude, 1995)
Akkerman, Ben ; Appel, Karel ; Armando ; Asselbergs, Gustave ; Benner, Gerrit ; Beutener, Jan ; Brands, Eugène ; Constant ; Content, Eli ; Corneille ; Couzijn, Wessel ; Daniels, René ; Dekkers, Ad ; Dibbets, Jan ; Diederen, Jef ; van Elk, Ger ; Engels, Pieter ; Fernhout, Edgar ; Freijmuth, Alphons ; de Goede, Kees ; van Golden, Daan ; Gudmundsson, Sigurdur ; Hillenius, Jaap ; van Hoek, Hans ; van Koningsbruggen, Rob ; Lataster, Ger ; Lucassen ; Lucebert ; Nanninga, Jaap ; Ouborg, Pieter ; Roeland, Jan ; Rogge, Cornelius ; Schippers, Wim T. ; Schoonhoven, Jan ; Sierhuis, Jan ; Struycken, Peter ; Tajiri, Shinkichi ; Verhoef, Toon ; Verkerk, Emo ; Visch, Henk ; Visser, Carel ; Volten, André ; Wagemaker, Jaap ; Westerik, Co
biog., bibliog. p. 242-246
De Nederlandse identiteit in de kunst na 1945, Stedelijk Museum Amsterdam, 16.12.1984 - 15.04.1985, Rijksmuseum Vincent Van Gogh, Amsterdam
Nederlands
boek
Keywords: Nederland